A new community–based context distribution approach for large–scale pervasive systems. (18th September 2013) - Vahdat–Nejad, Hamed; Zamanifar, Kamran; Nematbakhsh, Nasser
In large–scale pervasive computing environments, a huge amount of context is continuously created by context sources and as required by context consumers. Scalability is a challenge for managing and distributing this amount of data. In this research, a new scheme for context distribution is proposed which is based on forming context consumer communities to improve scalability. The main feature of members of a community is pursuing the same context types. After constituting the consumer communities, the context–distribution system makes use of a push–based approach for distributing context information among interested entities. Experimental results show the efficiency of the proposed scheme in large–scale environments.